A Tunable Z-Shaped Channel Gradient Metamaterial for Enhanced Detection of Weak Acoustic Signals - Yulin Ren; Guodong Hao; Xinsa Zhao; Jianning Han (Crystals)
Acoustic sensing technology has attracted significant attention across various fields, including mechanical fault early warning and wireless communication, due to its high information density and advantages in remote wireless applications. However, environmental noise reduces the signal-to-noise ratio (SNR) in traditional acoustic systems. In response, this article proposes a novel Z-shaped channel gradient metamaterial (ZCGM) that leverages strong wave compression effects coupled with effective medium theory to detect weak signals in complex environments. The properties of the designed metamaterials were verified by theoretical derivation and finite element simulation of the model. Compared to conventional linear gradient acoustic metamaterials (GAMs), ZCGM demonstrates significantly superior performance in acoustic enhancement, with a lower capture frequency. Furthermore, the structure exhibits flexible tunability in its profile. In addition, the center frequency of each actual air gap is determined in this paper based on the swept frequency signal test. Based on this center frequency, a preset specific harmonic acoustic signal is used as an emission source to simulate the actual application scenario, and experiments are constructed and conducted to verify the performance of the designed metamaterials. The results consistently show that ZCGM has distinct advantages and promising application prospects in the detection, enhancement, and localization of weak acoustic signals.